Exploring the Antimicrobial Potential of Cyperus rotundus Extract Against Multidrug-Resistant Escherichia coli in Urinary Tract Infections - Luxy, C. J.; Sumathi, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The widespread use of antibiotics has contributed to the emergence of antibiotic-resistant bacteria, including Escherichia coli (E. coli), a primary cause of urinary tract infections (UTIs). The increasing antimicrobial resistance levels have prompted research into alternative treatments, such as medicinal plants, to counter this global health concern. This study aimed to evaluate the effectiveness of solvent extracts from Cyperus rotundus (C. rotundus) against multidrug-resistant strains of E. coli associated with UTIs, as well as examine the phytochemical characteristics of the plant extract. E. coli isolates from pregnant women with UTIs were collected from several clinical laboratories, and their antibiotic resistance levels were evaluated. The antimicrobial activity of the C. rotundus extract was assessed using the agar-well diffusion method. In addition, GC-MS analysis was employed to screen for qualitative phytochemicals and secondary metabolites. The C. rotundus extract demonstrated significant inhibitory results on the resistant isolates, with a zone of inhibition ranging from 9mm to 17mm. The extract was found to contain various phytochemicals such as alkaloids, flavonoids, phenolics, tannins, and triterpenoids. GC-MS analysis detected bioactive compounds such as 3, 4-Altrosan, Phytol, Isoquinoline, and beta-sitosterol. These findings show that C. rotundus has the potential to be a valuable resource in the fight against antibiotic-resistant UTIs, underscoring the need for further investigation.